Kazakh intelligentsia in the early ХХ-th century and the national idea (Journal of history, 2017)
In XXth Century the Muslim movement Turk and Muslim peoples against the colonialist yoke of imperial power had democratic character based on the national, cultural and political demands. It was the ideology of the movement of Turk and Islamic Defenders parties. The formation of the Muslim movement was caused by intolerable and colonizing burdens, poor sociopolitical situation of Turk and other Muslim nations under Rus sian colony. The colonial policy the imperial power aimed at Russification of all spheres of social life led to the crisis and stalemate life of Muslim na tions under the empire. This angered the Muslims and encouraged them to fight for independence. And also by assessing the connection between the Turkic consolidation and the current political situation, movements of di rection and ideas aimed at uniting the Turkic peoples are determined. The main purpose of this study is to analyze the activities of representatives of the national intelligentsia and the revival of national ideologies. The activity of representatives of the national intelligentsia in the early XXth century in the formation of the national idea was considered in the article.